Space Utilization Control on Cultural Activities in the Coastal Border Area of Rembang Regency - Yulianti, Shania Ayu Nur; Mulyaningrum, Edith Ratna (Fakultas Syariah INSURI Ponorogo, 2024)
The coastal border region of Rembang regency has many cultivation practices that contradict the intended purpose and designated use of that area. this will threaten the sustainability of the coast either directly or indirectly. This study aims to find out the factors the cause of space utilization in the coastal boundary area that is not in accordance with the established spatial plan, the obstacles faced and the efforts made by the Regional Government in controlling the coastal border area so that it is suitable for its designation. This study uses a qualitative method with an empirical juridical approach. Primary data sources were obtained through interviews. While secondary data obtained from legislation, books, journals. The results of this study indicate because the increasingly complex needs of the Rembang community are not accompanied by the availability of land. Some of the obstacles faced by local governments in controlling coastal border areas so that they are suitable for their designation are the lack of implementation of the provisions of incentives and disincentives as well as the imposition of administrative sanctions, the establishment of PPNS. The regional government made several efforts, including conducting socialization, conducting site reviews, providing land rights status for permitted activities.